FAKTOR YANG MEMPENGARUHI PERILAKU PELANGGAN YANG BERKUNJUNG KE RESTORAN CEPAT SAJI DI KOTA BATAM - Sihombing , Dame Afrina (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023, 2023)
The latest phenomenon that has arisen from the rapid development of technology in the culinary business is that people can order food directly via smartphones and receive orders delivered by courier services, all of which are combined in one mobile application. According to an Australian research institute, 55 million Indonesians buy food at fast food restaurants and family restaurants. This indicates that many people prefer to order food rather than cook it themselves for practical reasons. This study aims to determine the behavior of fast-food restaurant customers in Batam City after the Covid-19 pandemic by considering 4 variables, namely atmosphere, service quality, food quality and price. A sample of 210 people in this study were residents of Batam City who had visited fast food restaurants. This study uses primary data collected by distributing questionnaires in Google form format. Distribution media include Whatsapp, Line, and Instagram. Tests carried out using the SPSS application. The results of this study indicate that the price and atmosphere variables have a significant effect on behavioral intentions. On the other hand, the variables of food quality and service quality do not show a significant effect. Keywords: atmosphere, quality service, food quality, behavioral intention.